Strengthening Financial Resilience and Cybersecurity Awareness Among Indonesian Migrant Workers in Hong Kong: A Digital Financial Literacy Community Service Program - Emeralda Ayu Kusuma; Ikhsan Budi Riharjo; Ardilla Ayu Kirana; Annisa Amalia Raharja (Green Publisher Indonesia, 2026)
Indonesian Migrant Workers (PMI) increasingly use digital financial services for remittances, savings, payments, and family financial management. However, access to digital services is not always accompanied by adequate financial literacy and cybersecurity awareness. This community service program aimed to strengthen PMI's practical capacity in personal financial management, debt control, simple investment screening, digital financial recording, and protection from cyber risks. The activity was conducted online via Zoom Meeting on 21 October 2025, with 90 PMI participants in Hong Kong. The method combined interactive counseling, case simulation, application demonstration, guided practice, discussion, and pre-test–post-test evaluation. The results show improvement across all measured indicators: understanding of personal financial management increased from 48 percent to 82 percent, debt and simple investment literacy from 42 percent to 79 percent, ability to recognize digital fraud from 39 percent to 76 percent, ability to use digital financial applications from 35 percent to 71 percent, and awareness of personal data security from 44 percent to 85 percent. The program indicates that integrated financial and digital literacy education can support migrant workers' financial resilience and safer participation in the digital economy.